2021
DOI: 10.3390/s21113925
|View full text |Cite
|
Sign up to set email alerts
|

Medical Images Encryption Based on Adaptive-Robust Multi-Mode Synchronization of Chen Hyper-Chaotic Systems

Abstract: In this paper, a novel medical image encryption method based on multi-mode synchronization of hyper-chaotic systems is presented. The synchronization of hyper-chaotic systems is of great significance in secure communication tasks such as encryption of images. Multi-mode synchronization is a novel and highly complex issue, especially if there is uncertainty and disturbance. In this work, an adaptive-robust controller is designed for multimode synchronized chaotic systems with variable and unknown parameters, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…They used their RGB images acquired using the Medipix3RX chip technology, a device used today in spectroscopic imaging systems. While Javan et al [33] defined an encryption method based on multi-mode synchronization of Chen hyper-chaotic systems applied to medical images, the authors used both standard benchmark images and their X-ray and CT images of COVID-19 patients, but they only reported the entropy values and the NPCR and UACI metrics for the CT image dataset. To show the differences of the datasets of each work, in Table 2 we show the imaging modality, the number of images, the color composition (RBG or grayscale), and the image sizes in pixels (px) of each image dataset used by the authors to be compared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They used their RGB images acquired using the Medipix3RX chip technology, a device used today in spectroscopic imaging systems. While Javan et al [33] defined an encryption method based on multi-mode synchronization of Chen hyper-chaotic systems applied to medical images, the authors used both standard benchmark images and their X-ray and CT images of COVID-19 patients, but they only reported the entropy values and the NPCR and UACI metrics for the CT image dataset. To show the differences of the datasets of each work, in Table 2 we show the imaging modality, the number of images, the color composition (RBG or grayscale), and the image sizes in pixels (px) of each image dataset used by the authors to be compared.…”
Section: Discussionmentioning
confidence: 99%
“…It uses a high-speed permutation process followed by an adaptive diffusion. Javan et al [33] proposed a medical image encryption method based on multi-mode synchronization of hyper-chaotic systems, where their main contribution was to encrypt medical images based on robust adaptive control. In [34] Xue et al proposed an image protection algorithm based on the deoxyribonucleic acid chain of dynamic length.…”
Section: Introductionmentioning
confidence: 99%
“…Mehta et al [20] suggested a robust scheme for fundus images based on chaos theory utilizing a grouping of permutation and substitution design, which has applications in medical image cryptography, such as the encryption of fundus images. Using robust adaptive control, Javan et al [21] developed a solution based on hyper-chaotic systems' multi-mode synchronization to encrypt medical images. On the contrary, Moafimadani et al [22] offered a technique based on chaotic maps to secure medical images from hacking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Javan et al [86] showed a synchronization scheme using a robust-adaptive control procedure with the help of the Lyapunov stability theorem and the experimental results revealed the capability and fexibility of this method in synchronization of chaotic systems. Later, Javan et al [87] developed an adaptive control method, and the defnition of appropriate Lyapunov function was used for synchronization for chaotic systems; the results showed the efectiveness of the proposed synchronization technique in the medical images encryption for telemedicine application. One more piece of research was introduced by Wang and Rongwei [88], where they applied the adaptive control method to investigate the design of a universal controller to achieve the hybrid synchronization of a class of chaotic systems; numerical examples verify and validate the efectiveness of the proposed theoretical results.…”
Section: Active Controlmentioning
confidence: 99%